(E)-1-(2,4,6-Trihydroxybenzylidene)-4-ethylthiosemicarbazide dihydrate - Tan, K.W.; Ng, S.W.; Shawish, H.B.; Maah, Mohd Jamil (International Union of Crystallography, 2010)
In the title molecule, C(10)H(13)N(3)O(3)S center dot 2H(2)O, the thiosemicarbazide =N-NH-C(=S)-NH- fragment [torsion angle = 0.2 (1)degrees] is nearly coplanar with the benzene ring [dihedral angle = 2.4 (1)degrees]. The benzene ring and semicarbazide moiety are located on opposite sites of the C=N bond, showing an E configuration. The hydroxy, imino and water H atoms are engaged in extensive hydrogen bonding, forming a three-dimensional network.